1993
DOI: 10.2307/3578395
|View full text |Cite
|
Sign up to set email alerts
|

DNA Strand Break Induction and Rejoining and Cellular Recovery in Mammalian Cells after Heavy-Ion Irradiation

Abstract: The induction of intracellular DNA strand breaks by X rays and various heavy charged particles was measured by the alkaline unwinding and alkaline and neutral filter elution techniques. No variations in strand break induction were found between the different cell lines under investigation. For a given particle, both the LET and the particle energy determined the efficiency to induce DNA lesions. RBE values for the total amount of induced strand breaks were always less than 1. For DNA double-strand breaks (DSBs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(22 citation statements)
references
References 41 publications
1
20
1
Order By: Relevance
“…This obscures the true extent comparable energy and linear energy transfer value (18,20,29). Our data clearly indicate higher yields of of the ''tail'' of DNAs at the small molecular length edge of the 1.3-Mbp group, producing an underestimate of DSBs per dose induced by Fe 26/ than by g rays, more in agreement with the data of Kampf (20), who used the number of these small molecules in the group.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…This obscures the true extent comparable energy and linear energy transfer value (18,20,29). Our data clearly indicate higher yields of of the ''tail'' of DNAs at the small molecular length edge of the 1.3-Mbp group, producing an underestimate of DSBs per dose induced by Fe 26/ than by g rays, more in agreement with the data of Kampf (20), who used the number of these small molecules in the group.…”
Section: Resultssupporting
confidence: 81%
“…This results in an overestimate of the number average mo-sucrose gradient sedimentation to measure DSB frequencies, than with those of Lobrich et al, who mealecular length, and thus an underestimate of the frequency of double strand breaks. Thus, we limit the sured depletion of a radioactively probed NotI cleavage population on CHEF gels (29), or of Heilmann et al, range of the current assay, for human DNA cleaved with NotI and electrophoresed using this TAFE regime, who used neutral elution (18). to Ç30 DSB/Gbp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies showed that clustered DSBs lesions induced by Fe particles are dif2icult to be repaired and resulting in elevated chromosome instability and enhanced cellular radiosensitivity (40,41) . The dif2iculty of repairing the clustered DSBs may due to the nature of the complex DNA damage induced by dense ionizations along the HZE particle track (19,22,(42)(43)(44)(45) . In mammalian cells, DNA DSBs are repaired mainly by two distinct pathways: nonhomologous end joining (NHEJ) and homologous recombination (HR).…”
Section: The Repair Pathways Of Clustered Dna Damage Induced By Hze Pmentioning
confidence: 99%
“…There is literature evidence that DSB repair in cells irradiated with high-LET IR is less efficient than in the case of low-LET radiation. This is due, exclusively, to the complexity of these breaks (Heilmann et al, 1993;Dianov et al, 2001). Tandems of different single lesions with DSB may further complicate the repair of both types of injury and increase their biological significance (Sutherland et al, 2000;Sage and Harrison, 2011).…”
Section: Introductionmentioning
confidence: 99%